Features of lipid metabolism in patients with erosive esophagitis during the period of martial law - L.M. Mosiychuk; I.A. Klenina; O.P. Petishko (Gastroenterologìa)
Background. Over the past decades, the number of patients with erosive esophagitis in the world has increased. At the same time, metabolic syndrome and chronic stress are considered risk factors for the development of erosive esophagitis. The aim of the study: to determine the diagnostic significance of lipid metabolism indicators for the formation of a group at risk of developing erosive esophagitis among patients with gastroesophageal reflux disease and overweight during the period of martial law. Materials and methods. The study included 40 men with gastroesophageal reflux disease and overweight. The subjects were aged from 20 to 57 years, the average age was (42.8 ± 1.2) years. According to the results of esophagogastroduodenoscopy with narrow band imaging, 25 patients were diagnosed with erosive esophagitis, and 15 with non-erosive reflux disease. The serum levels of total cholesterol (TC), triglycerides (TG), and high-density lipoprotein cholesterol (HDL-С) were determined in all subjects using a Stat Fax 4500 biochemical analyzer (USA). Low-density lipoprotein cholesterol (LDL-C), very low-density lipoprotein cholesterol (VLDL-C) and atherogenic index (AI) were also calculated. Results. The average group content of TC in the blood serum of patients with erosive esophagitis was 1.2 times higher compared to the control group (p = 0.0083) due to the presence of hypercholesterolemia in 36.0 % of patients. Despite the fact that the median TG content in both groups did not exceed the reference values, hypertriglyceridemia was noted in 32 % of participants with erosive esophagitis. In addition, these patients, in contrast to the control group, had a significant decrease in HDL-C levels by 1.4 times (p = 0.0042) with a simultaneous 2-fold increase in VLDL-C (p = 0.0024) and a 1.8-fold in AI (p = 0.0069). In patients with erosive esophagitis, the ratios of TG/HDL-C, LDL-C/HDL-C and TC/HDL-C were, respectively, 1.4 times (p = 0.0246), 1.3 times (p = 0.0295) and 1.2 times (p = 0.0085) higher than in patients with non-erosive reflux disease. Patients with erosive esophagitis had direct correlations between body mass index and TG/HDL-C (r = 0.47; p = 0.0003), LDL-C/HDL-C (r = 0.34; p = 0.011) and TC/HDL-C (r = 0.44; p = 0.0007). Conclusions. The diagnostic criteria for the formation of a group at risk of developing erosive esophagitis among patients with gastroesophageal reflux disease and overweight during the period of martial law are the ratios of TG/HDL-C (sensitivity 78.6 %, specificity 87.5 %), TC/HDLC (sensitivity 82.1 %, specificity 62.5 %), LDL-C/HDL-C (sensitivity 75.0 %, specificity 56.2 %). Therefore, in case of contraindications or limited access to esophagogastroduodenoscopy, it is necessary to study lipid metabolism indicators and their correlations in patients with gastroesophageal reflux disease and overweight.